Conscious prone positioning in a pregnant patient with COVID-19 respiratory distress: A case report and review - Erica Testani; Sara Twiehaus; Thaddeus Waters; Xavier Pombar (Elsevier, 2021)
Prone positioning has been used for decades to improve oxygenation in patients with acute respiratory distress syndrome. With the COVID-19 pandemic there has been a growing emphasis on the utilization of prone positioning for non-intubated patients as a means of preventing invasive ventilation and improving outcomes. In this case report, a patient is presented with acute hypoxemic respiratory failure in late pregnancy who experienced significant improvements in oxygenation with prone positioning. Additionally, the physiology of prone positioning is reviewed, as well as its mechanism and safety in pregnancy.